2021
DOI: 10.3390/polym13172934
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Infill Pattern on Mechanical Behavior of Polymeric and Composites Specimens Manufactured Using Fused Filament Fabrication Technology

Abstract: This paper presents the results of a comparative evaluation of the tensile strength behaviors of parts obtained by additive manufacturing using fused filament fabrication (FFF) technology. The study investigated the influences of the deposition printing parameters for both polymers and fiber-reinforced polymers. Polymeric materials that are widely used in FFF were selected, including acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), and nylon. Carbon and glass continuous fibers were used to reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…Apart from the filling density and patterns, there are numerous studies on the influence of the printing deposition direction and build-up on the mechanical properties of biopolymers [ 160 , 161 ]. These influences have been investigated by Dezaki et al from different build-up directions in two directions: flat and at the edge ( Figure 23 ).…”
Section: Influence Of the Structure And/or Inner Structure On Part Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the filling density and patterns, there are numerous studies on the influence of the printing deposition direction and build-up on the mechanical properties of biopolymers [ 160 , 161 ]. These influences have been investigated by Dezaki et al from different build-up directions in two directions: flat and at the edge ( Figure 23 ).…”
Section: Influence Of the Structure And/or Inner Structure On Part Pr...mentioning
confidence: 99%
“…FEA results showed that honeycomb and lattice patterns were the strongest among the other patterns, while they had lower weight [ 160 ]. Martin et al [ 161 ] investigated the influences of the printing deposition on the tensile properties of PLA samples. The yield modulus values obtained in the tensile test showed a decrease of 15.96% with concentric deposition and 27.07% with zigzag deposition compared to the manufacturer’s data [ 161 ].…”
Section: Influence Of the Structure And/or Inner Structure On Part Pr...mentioning
confidence: 99%
“…With a wide range of materials and technologies, additive manufacturing has proven to be one of the most efficient alternatives to traditional manufacturing. The set of technologies involved in AM aim to achieve the characteristics required for printed parts, both in design features and mechanical performance (Martín et al [ 1 ]), taking advantage of the possibilities that these processes offer: cost and waste reduction, design freedom, flexibility, printing-time reduction, use of a variety of materials, mechanical-property and surface-roughness improvement, etc. In this last aspect, unlike with original models, parts manufactured with fused filament fabrication (FFF) technology present an inherent superficial texture due to its distinctive layer-by-layer deposition (Buj-Corral et al [ 2 ], Delfs et al [ 3 ]), which can be considered a surface-finish defect.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D FDM prints are mainly tested for their mechanical properties [16][17][18][19]. However, papers analyzing the tribological properties of FDM 3D prints are appearing more frequently [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%